UPAYA PENINGKATAN DAYA DUKUNG LINGKUNGAN MELALUI PENERAPAN PRINSIP SUSTAINABLE DEVELOPMENT BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Cahyani, ferina Ardhi (Indonesian State Law Review (ISLRev), 2020)
Environmental problems are increasing every day. This results in a decrease in the carrying capacity of the environment. Population growth also puts a burden on the carrying capacity of the environment. To improve the quality of carrying capacity, it is necessary to implement the principle of sustainable development. With the implementation of sustainable development principles that balance economic, social and environmental aspects, the quality of the carrying capacity of the environment will be better so that the availability of natural resources for future generations will be guaranteed.